Comparative analysis of psychophysiological features of taekwondo athletes of different age groups - Leonid Podrigalo; Vyacheslav Romanenko; Olha Podrihalo; Sergii Iermakov; Anatolyi Huba; Volodymyr Perevoznyk; Olexandr Podavalenko (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. The importance of psychophysiological features in optimizing the functional state of athletes is beyond doubt. The aim of this study was a comparative analysis of the psychophysiological features of taekwondo athletes of different age groups.